2000
DOI: 10.1007/s004290000090
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-regulated protein 78 (GRP78) is elevated in embryonic mouse heart and induced following hypoglycemic stress

Abstract: This study investigates the distribution and heart levels of glucose regulated protein (GRP) 78 during normal development and in response to hypoglycemia in the mouse. Results demonstrate that GRP78 is strongly expressed with in the heart, neural tube, gut endoderm, somites, and surface ectoderm of mouse embryos during early organogenesis, and GRP78 staining remains prominent in the heart from gestational days 9.5 through 13.5. Cardiac myocytes are the primary site of GRP78 expression within the heart. GRP78 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…In support of this notion, high levels of GRP78 were detected in the heart, somite, and neural tube of developing mouse embryos at day 9.5 and day 10.5 (2). Elevated levels of GRP78 in the testes also imply that GRP78 might play an important role in spermatogenesis (14).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In support of this notion, high levels of GRP78 were detected in the heart, somite, and neural tube of developing mouse embryos at day 9.5 and day 10.5 (2). Elevated levels of GRP78 in the testes also imply that GRP78 might play an important role in spermatogenesis (14).…”
Section: Discussionmentioning
confidence: 79%
“…1A). The expression profile of the 3kb/LacZ transgene has been shown to faithfully represent endogenous GRP78 expression in mouse embryos at E9.5 to E11.5, where GRP78 is highly elevated in the developing heart and in somite and neural tubes (2,33). LacZ activity, as detected by ␤-gal staining, was observed in both the trophectoderm (TE) and inner cell mass (ICM) of the 3kb/LacZ blastocyst (Fig.…”
Section: De Novo Transcription Of Grp78 In Blastocysts Requires the Ementioning
confidence: 89%
“…Tsang et al (2007) report delayed terminal differentiation in hypertrophic chondrocytes of the growth plate in response to ER stress, brought on by the retention of collagen type X in the ER. Additionally, it is reported that grp78 is upregulated during early mouse development in the heart, somites, and other tissues, and that its expression decreases during later phases of development (Barnes and Smoak 2000). It has also been suggested that the GRP family of proteins serve as detectors for the level of activity of cellular secretion (Kozutsumi et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…For example, reduction of ER Ca increases GRP78 in H9c2 cardiac myocytes 13 and activates ATF6 and the GRP78 promoter in cardiac myocyte cultures. 14 GRP78 is also elevated in the embryonic mouse myocardium, 15,16 and XBP1 knockout mice die in utero from cardiac myocyte apoptosis, 17 suggesting a requirement for the UPR during cardiac development. GRP78 is induced in mouse hearts on transverse aortic constriction, 18 suggesting UPR activation by pressure overload.…”
mentioning
confidence: 99%